(untitled) (Journal Resuscitatio Balcanica, 2025)
Aims: This study aimed to identify predictors of prehospital outcomes, specifically initial shockable rhythms and return of spontaneous circulation, in out-of-hospital cardiac arrest cases witnessed by emergency medical services. Materials and Methods: The study utilized epidemiological data collected via EuReCa questionnaires from October 1, 2014, to December 31, 2021. It included patients treated by EMS, covering both pediatric cases and non-cardiac causes of cardiac arrest. Data from 16 municipalities in Serbia, representing 24.13% of the population, were analyzed using SPSS Statistics. Statistical significance was defined as p<0.05. Results: Among 8,349 out-of-hospital cardiac arrest cases analyzed, we found that 12.2% cases were witnessed by emergency medical teams. The likelihood of recording an initially shockable rhythm in this category of witnessed cases was 2.35 times higher for individuals older than 65 compared to younger ones (OR: 2.354; 95% CI: 1.280-4.331), 2.19 times higher in the case of incidents involving males compared to females (female gender: OR: 0.457, 95% CI: 0.242-0.864), and 22.69 times higher in the case of cardiogenic etiology (OR: 22.695; 95% CI: 3.020-170.547). The likelihood of achieving return of spontaneous circulation (ROSC) is 3.23 times higher for incidents occurring outside the residence area (within residence: OR: 0.310; 95% CI: 0.176-0.546) and 4.07 times higher in the case of initially recorded shockable rhythm (OR: 4.068; 95% CI: 2.273-7.278). If the incident occurs in a location with fewer than 100,000 residents, outside the residence area, and if the initial rhythm is shockable, the likelihood of ROSC at admission is higher, but none of these variables emerged as independent predictors. Conclusion: One of the proposed strategies to improve the survival of out-of-hospital cardiac arrest is to increase the incidence of EMS-witnessed arrests as the category of events according to the evidence with the best survival. Additional research on predictors of desired prehospital outcomes is necessary, as well as identification of risky epidemiological categories, for further planning activities and increasing survival in this group of patients, as well as in epidemiological categories with high risks and negative predictive outcomes.